HOW DOES DIGITAL FINANCIAL LITERACY RELATE TO THE FINANCIAL PERFORMANCE OF MSMES TOURISM FIRMS? THE MEDIATING ROLE OF FINANCIAL BEHAVIOR - Awwaliyah, Intan Nurul; Sumani, Sumani; Singgih, Marmono; Widodo, Roni (Fakultas Ekonomi dan Bisnis, UNTAN, 2023)
MSMEs play a significant role in the digital economy. This highlights the need for governments to focus on their development beyond financing and improving their digital literacy. This study investigates the impact of digital financial literacy on the financial performance of MSMEs at Pancer Puger Beach, Jember, with a specific focus on the role of financial behavior in promoting this relationship. This study used a mixed method with an exploratory sequential design combining qualitative data gathered from focus group discussions, in-depth interviews, and observations. Quantitative data were collected through questionnaires from 120 MSMEs respondents obtained via snowball sampling and analyzed using the partial least squares method. The results show that (1) Digital financial literacy affects financial performance, (2) Digital financial literacy affects financial behavior, and (3) Financial behavior affects the financial performance of MSMEs, while financial behavior serves as a mediator between financial literacy and financial performance. The findings suggest that tourism MSMEs can adapt and thrive in line with Indonesia's digital financialization.JEL: G41, L26, L83.